2016
DOI: 10.1017/s1751731115002220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between linear and proportional hazard models for the analysis of age at first lambing in the Ripollesa breed

Abstract: Age at first lambing (AFL) plays a key role on the reproductive performance of sheep flocks, although there are no genetic selection programs accounting for this trait in the sheep industry. This could be due to the non-Gaussian distribution pattern of AFL data, which must be properly accounted for by the analytical model. In this manuscript, two different parameterizations were implemented to analyze AFL in the Ripollesa sheep breed, that is, the skew-Gaussian mixed linear model (sGML) and the piecewise Weibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…In the present study was observed notorious phenotypic and permanent environment variation for all traits analyzed, which consequently affects the magnitude of the additive genetic component. Estimated ℎ 2 of AFL trait was 0.13 ± 0.10, which is in accordance to the findings of Casellas [16] in Ripollese sheep, using Bayesian inference (Piecewise Weibull Proportional Hazards models). Also, in a study by Ono [18], considering data from the same population studied in this research, but without including a permanent environment effect, obtained a moderate heritability (0.24 ± 0.05), also by a Bayesian approach.…”
Section: Variance Components and Genetic Parameterssupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study was observed notorious phenotypic and permanent environment variation for all traits analyzed, which consequently affects the magnitude of the additive genetic component. Estimated ℎ 2 of AFL trait was 0.13 ± 0.10, which is in accordance to the findings of Casellas [16] in Ripollese sheep, using Bayesian inference (Piecewise Weibull Proportional Hazards models). Also, in a study by Ono [18], considering data from the same population studied in this research, but without including a permanent environment effect, obtained a moderate heritability (0.24 ± 0.05), also by a Bayesian approach.…”
Section: Variance Components and Genetic Parameterssupporting
confidence: 87%
“…Numerous studies on the estimation of genetic parameters for "local" breeds of sheep were performed considering reproductive traits related to prolificacy: litter size at birth, litter size at weaned, total litter weight at birth, total litter weight at weaned [6][7][8][9][10][11][12][13]; survivability at weaning age [14,15]; and for the age at first lambing [16].…”
Section: Introductionmentioning
confidence: 99%
“…Survival analysis by proportional hazard models (Cox, 1972) must be viewed as an emerging statistical tool in the animal science framework with remarkable applications to several domestic species (Ducrocq et al, 1988a(Ducrocq et al, ,b, 2000Sánchez et al, 2006;Fernàndez de Sevilla et al, 2008) and economically relevant traits (Schneider et al, 2005;Zavadilová and Štípková, 2013;Casellas, 2016). The weight of functional characters such as survival or longevity in selection indexes has increased during recent decades (Serenius et al, 2006;Forabosco et al, 2009), given their close relation with culling costs (Stott, 1994;Horn et al, 2012) and society's concern for the well-being of domestic animals (Camm and Bowles, 2000).…”
Section: Technical Notementioning
confidence: 99%